Tibial healing after secondary alveolar bone grafting: Usefulness of ultrasonography. Issue 3 (May 2020) - Hanai, Hiroyuki; Kurita, Kenichi; Imaoka, Koki; Mizuno, Shoya; Matsui, Yoshihito; Katayama, Yoshiko; Maeda, Masahito; Nakayama, Atsushi; Abe, Atsushi; Ariji, Yoshiko; Ariji, Eiichiro
Abstract: Objective: Both clinical and X-ray findings have been used for postoperative assessment of the donor site following secondary alveolar bone grafting in our department. However, this approach requires that patients be exposed to X-ray irradiation several times at the donor site and the cleft site. Furthermore, the findings do not depict bone healing status in detail and thus offer little information to help in deciding the required duration of postoperative movement restriction. Therefore, we sought to determine the utility of ultrasound in addition to X-ray for evaluating bone surface healing at the donor site. Methods: Subjects were 17 patients (9 boys and 8 girls; median weight of harvested bone, 7.5 g) who underwent alveolar bone grafting using tibial grafts. All cases were evaluated on X-ray and ultrasound images. Results: Agreement between the X-ray and ultrasound assessments was 88.2 % (15/17) at postoperative month 3 and 70.6 % (12/17) at postoperative month 6. No significant differences were observed, but the time required for healing tended to be longer when the weight of harvested bone was larger. Conclusions: Ultrasound was a useful modality in postoperative assessment, and the combined use of ultrasound and X-ray examination was found to enable reduced exposure to X-ray irradiation and close observation of the bone surface. Also, movement restriction of ≥1 month appeared necessary, and the time to healing was longer for a larger weight of harvested bone.